Rebooting policy analysis strengthening the foundation, expanding the scope - Linquiti, Peter D. (Sage Publications, 2023)
Rebooting Policy Analysis: Strengthening the Foundation, Expanding the Scope is a savvy introduction to policy analysis that gets students thinking, not just about how decisions should be made, but how they are made. The text highlights practical skills needed to advise decision-makers on matters of public policy in ways that are well-informed and solutions-oriented, while managing limitations like time, resources, and information. In a world that has become increasingly complex and partisan, the strength of policy analysis rests not only in its classical academic methods, but on the development of a practical, analytic mindset.